1981
DOI: 10.1136/hrt.45.5.500
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias 48 hours before, during, and 48 hours after discharge from hospital following acute myocardial infarction.

Abstract: SUMMARYThe cardiac rate and rhythm were studied by 24-hour ambulatory electrocardiographic recording in 44 patients before, during, and after being discharged from hospital following an acute myocardial infarction. The first recordings were started 48 hours before discharge, the second on the morning of the day of discharge, and the third 48 hours after discharge (at home). While in hospital and after returning home the heart rate fell during sleep but there was no diurnal variation in the frequency of ventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…276 Sleep appears to be protective against arrhythmias, regardless of when it occurs, since HR and BP are decreased even during an afternoon nap or siesta. 277 As expected, loss of ANS circadian rhythmicity, e.g., as observed in AMI patients, 237 is reflected by absence of nocturnal decrease in VPBs, confirming again the protective role of sleep and its associated physiology against arrhythmias.…”
Section: Role Of Sleep On the Electrical Properties Of The Myocardium...supporting
confidence: 71%
See 1 more Smart Citation
“…276 Sleep appears to be protective against arrhythmias, regardless of when it occurs, since HR and BP are decreased even during an afternoon nap or siesta. 277 As expected, loss of ANS circadian rhythmicity, e.g., as observed in AMI patients, 237 is reflected by absence of nocturnal decrease in VPBs, confirming again the protective role of sleep and its associated physiology against arrhythmias.…”
Section: Role Of Sleep On the Electrical Properties Of The Myocardium...supporting
confidence: 71%
“…The observed nocturnal decrease in VPBs was found to be reproducible, as established through replicate 24-h ECG monitoring studies. 233,236 Only two studies 237,238 reported no nocturnal decrease in VPBs; however, altered sleep patterns 238 or absence of circadian rhythmicity in ANS activity 237 may have contributed to these contrasting findings. Another study documented a nocturnal peak of VPBs in only one-half the patient sample, but these findings were probably affected by hypertrophic cardiomyopathy.…”
Section: Circadian Rhythms Of Ventricular Premature Beats (Vpbs)mentioning
confidence: 99%
“…When sleep was monitored electroencephalographically, arrhythmias were most facilitated in REM sleep during the second half of the night [43] or in the transition from wakefulness to light sleep [24,48]. Other authors "failed to note any significant correlation between VPBs and different stages of the sleep-wake cycle or its transition periods [33,34,38,48]. Orr et al [38], however, emphasised that there is a marked variability in the incidence of arrhythmias not only among different subjects, but even within the same patient across nights.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%